Implementasi Metode Simple Additive Weighting (SAW) Dalam Penentuan Siswa Berprestasi di SDN 36 Lubuk Batu - Anggi Hadi Wijaya; Ipriadi (GLOBAL SCIENTS PUBLISHER, 2025)
The selection of outstanding students in elementary schools is a crucial process in education to provide appreciation and motivate students to achieve both academic and non-academic excellence. SDN 36 Lubuk Batu faces challenges in selecting outstanding students because assessments are not solely based on academic grades but also include other aspects such as discipline, participation in extracurricular activities, and social behavior. To address this issue, this study implements the Simple Additive Weighting (SAW) method as a decision support system for selecting outstanding students. The SAW method was chosen for its ability to process multiple criteria objectively by assigning specific weights to each assessment aspect. The study results indicate that implementing the SAW method enhances the accuracy, transparency, and efficiency of the student selection process. Thus, the implementation of the SAW method can be an effective solution for improving the quality of student selection systems in elementary schools..